Circumscription of the genus Vietanna Lee & Pham, 2021 (Cicadidae: Leptopsaltriini) resulting in the synonymy of Duffelsa Wang et al., 2023 - Lee, Young June (Zootaxa, 2023)
The genus Vietanna Lee & Pham, 2021 described based on Vietanna hanoiensis Pham & Lee, 2021 is circumscribed and redescribed. By this, Duffelsa Wang et al., 2023 syn. nov. is synonymized with Vietanna. Duffelsa orientalis (Distant, 1912), Duffelsa parvula Wang et al., 2023, Duffelsa grandia Wang et al., 2023, and Duffelsa rubida Wang et al., 2023 are transferred to Vietanna from Duffelsa to become Vietanna orientalis (Distant, 1912) comb. nov., Vietanna parvula (Wang et al., 2023) comb. nov., Vietanna grandia (Wang et al., 2023) comb. nov., and Vietanna rubida (Wang et al., 2023) comb. nov..